Experiencing anesthesia and surgery early in life impairs cognitive and behavioral development - Jia, Xuqin; Tan, Siyou; Qin, Yinying; Wei, Yi; Jiang, Yage; Pan, Sining; Li, Chunlai; Chen, Jing; Liu, Tianxiao; Xie, Yubo (Frontiers in Neuroscience, 2024)
Background: The impact of anesthesia and surgery on neurocognitive and behavioral development in infants and children remains inadequately understood. Objective: To investigate the impact of early-life exposure to general anesthesia and surgery on cognitive and behavioral development. Methods and materials: Children aged 0-3 years who underwent general anesthesia and surgical procedures between 2012 and 2015 were included. The cognitive and behavioral development of these children at ages 4-6 years was assessed. Age-, race-, and gender-matched children from the same geographic region, who did not undergo general anesthesia or surgery, served as the control group. The Wechsler Preschool Primary Scale of Intelligence, Fourth Edition (WPPSI-IV) was used to evaluate children's total intelligence quotient (FSIQ) and specific cognitive domains. The Gesell Development Schedules (GSCH) and Child Behavior Checklist (CBCL) were employed to assess behavioral and personality development. Additionally, the study analyzed the effects of various factors including anesthesia drugs, surgery duration, number of surgeries, age, weight, ethnicity, and gender on postoperative neurocognitive and behavioral outcomes. Results: The study included 447 children with anesthesia/surgical exposure (AS) and 459 children in the control group. Analysis of cognitive and behavioral development showed a significant difference in the working memory index (WMI) between the AS and control groups (P < 0.05). Exploratory findings indicated that children administered remifentanil exhibited lower developmental quotient (DQ) values, whereas those given fentanyl showed higher (worse) Child Behavior Checklist (CBCL) total scores. Moreover, increased anesthesia/surgical exposures, younger age and lower body weight at exposure, and longer surgery durations were associated with cognitive and behavioral developmental challenges. Conclusion: This study examined the impact of early-life exposure to surgery and anesthesia on postoperative cognitive and behavioral development. Findings indicate that higher frequency of exposure to surgery and anesthesia, younger age, and lower body weight at exposure could negatively influence cognitive and behavioral development. Furthermore, variations in the effects of different anesthetics on behavior and cognition were observed. Caution is advised regarding the use of opioid analgesics such as remifentanil and fentanyl for more rigorous clinical applications.